A 4-Month Whole-Systems Ayurvedic Medicine Nutrition and Lifestyle Intervention Is Feasible and Acceptable for Breast Cancer Survivors: Results of a Single-Arm Pilot Clinical Trial. (November 2020) - Dhruva, Anand; Wu, Cairn; Miaskowski, Christine; Hartogensis, Wendy; Rugo, Hope S; Adler, Shelley R; Kaptchuk, Ted J; Kelkar, Rucha; Agarawal, Sangeeta; Vadodaria, Amisha; Garris, Ellen; Hecht, Frederick M
Purpose: Ongoing symptoms and impairments in quality of life (QOL) among breast cancer survivors remain a significant problem. We tested the feasibility and acceptability of a manualized Ayurvedic nutrition and lifestyle intervention for breast cancer survivors. Methods: Eligible participants had Stage I–III breast cancer, underwent treatment within the past year that included chemotherapy, and were without active disease. The 4-month individualized Ayurvedic intervention included counseling on nutrition, lifestyle, yoga, and marma (like acupressure) during 8 one-on-one visits with an Ayurvedic practitioner. Feasibility and acceptability were the primary outcomes. QOL (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire [EORTC QLQ C30]) and symptoms—sleep disturbance (General Sleep Disturbance Scale [GSDS]), fatigue (Lee Fatigue Scale [LFS]), depressive symptoms (Center for Epidemiological Studies—Depression Scale [CES-D]), anxiety (Spielberger State-Trait Anxiety Inventory [STAI-S, STAI-T]), and stress (Perceived Stress Scale [PSS])—were measured prior to, at midpoint, and at the end of the 4-month intervention. Effect sizes (Cohen's d ) were calculated along with paired t tests comparing baseline to end of month 4 time points. Mixed effects models were used for repeated measures analyses. Results: Participants ( n  = 32) had a mean age of 48 years ( SD  = 10). Retention at the end of the intervention was 84%. Among those who completed the intervention ( n  = 27), adherence was high (99.5% of visits with practitioners attended). Large improvements were seen in QLQ-C30 emotional functioning ( d  = 0.84, P  < 0.001), QLQ-C30 cognitive functioning ( d  = 0.86, P  < 0.001), GSDS ( d  =   –1.23, P  < 0.001), and CES-D ( d  =   –1.21, P  < 0.001). Moderate improvements were seen in QLQ-C30 global health ( d  = 0.65, p  = 0.003), LFS ( d  =   –0.68, P  = 0.002), and PSS ( d  =   –0.75, P  < 0.001). No adverse events were observed due to the intervention. Conclusion: This 4-month Ayurvedic whole-systems multimodal nutrition and lifestyle intervention was feasible and acceptable for breast cancer survivors. Promise of clinical benefit was seen in terms of improvements in symptoms and QOL that warrants further investigation.